Frequent Spread of Plasmodium vivax Malaria Maintains High Genetic Diversity at the Myanmar-China Border, Without Distance and Landscape Barriers - Lo, Eugenia (J Infect Dis, 2017)
BACKGROUND: In Myanmar, civil unrest and the establishment of internally displaced person (IDP) settlements along the Myanmar-China border have impacted malaria transmission. METHODS: Microsatellite markers were used to examine source-sink dynamics for Plasmodium vivax between IDP settlements and surrounding villages in the border region. Genotypic structure and diversity were compared across the 3 years following the establishment of IDP settlements, to infer demographic history. We investigated whether human migration and landscape heterogeneity contributed to P. vivax transmission. RESULTS: P. vivax from IDP settlements and local communities consistently exhibited high genetic diversity within populations but low polyclonality within individuals. No apparent genetic structure was observed among populations and years. P. vivax genotypes in China were similar to those in Myanmar, and parasite introduction was unidirectional. Landscape factors, including distance, elevation, and land cover, do not appear to impede parasite gene flow. CONCLUSIONS: The admixture of P. vivax genotypes suggested that parasite gene flow via human movement contributes to the spread of malaria both locally in Myanmar and across the international border. Our genetic findings highlight the presence of large P. vivax gene reservoirs that can sustain transmission. Thus, it is important to reinforce and improve existing control efforts along border areas.